2018
DOI: 10.1063/1.5029324
|View full text |Cite
|
Sign up to set email alerts
|

Silicon doped hafnium oxide (HSO) and hafnium zirconium oxide (HZO) based FeFET: A material relation to device physics

Abstract: The recent discovery of ferroelectricity in thin film HfO2 materials renewed the interest in ferroelectric FET (FeFET) as an emerging nonvolatile memory providing a potential high speed and low power Flash alternative. Here, we report more insight into FeFET performance by integrating two types of ferroelectric (FE) materials and varying their properties. By varying the material type [HfO2 (HSO) versus hafnium zirconium oxide (HZO)], optimum content (Si doping/mixture ratio), and film thickness, a material rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(68 citation statements)
references
References 22 publications
4
64
0
Order By: Relevance
“…The gate stack of MFIS should be regarded as MFI(IL)S, as shown in in Figure 2a, where F, I, IL, S are connected in series. The IL is an interfacial layer between I and S which is formed during the ferroelectric crystallization annealing process of FeFETs [8,39,[55][56][57]. The main component of IL is silicon dioxide with an electric permittivity (ε IL ) of ε IL = 3.9.…”
Section: Reason For Using Sbt In Fefetmentioning
confidence: 99%
“…The gate stack of MFIS should be regarded as MFI(IL)S, as shown in in Figure 2a, where F, I, IL, S are connected in series. The IL is an interfacial layer between I and S which is formed during the ferroelectric crystallization annealing process of FeFETs [8,39,[55][56][57]. The main component of IL is silicon dioxide with an electric permittivity (ε IL ) of ε IL = 3.9.…”
Section: Reason For Using Sbt In Fefetmentioning
confidence: 99%
“…CMOS compatible FeFET employing silicon (Si) transistors and Al doped HfO 2 as ferroelectric material were recently reported [3]- [5]. Ferroelectric gate thin film transistors (FeTFT) were developed using different ferroelectrics such as PZT [6]- [10], poly(vinylidene fluoridetrifluoroethylene) [P(VDF-TrFE)] [11]- [14], (Bi,La) 4 Ti 3 O 12 (BLT) [15] or HfO 2 -based materials (e.g., Si-doped or Zr-doped HfO 2 ) [16]- [19]. In terms of architecture, the [P(VDF-TrFE)] based FeTFT devices are generally top-gate, whilst the fully inorganic structures are bottom-gate.…”
Section: Introductionmentioning
confidence: 99%
“…Since the breakthrough of Böscke et al [20], which reported in 2011 the ferroelectricity of Si-doped HfO 2 , incremental focused researches have been performed in order to asses if HfO 2 based-materials can overcome some of the limitations of conventional ferroelectrics (such as PZT), markedly their (i) reduced compatibility with metaloxide-semiconductor (CMOS) technologies or (ii) limited scalability. The ferroelectricity of HfO 2 films manifests when the layer thickness is reduced to few nm (e.g., 10 nm) [16], [21]. However, this could generate an important technological hindrance, since a non-uniformity of only 1 nm will correspond to a thickness variation of 10%, with a negative impact on the overall performance reproducibility.…”
Section: Introductionmentioning
confidence: 99%
“…Various dopants influence the stabilization of the ferroelectric phase in hafnia thin films, for example, silicon (Si) [17,31,32], and such influence becomes more decisive in deep trench structures while the dopants concentration may change inside the HAR structure. Remarkably, it is more critical in low-doped materials, where such a low Si content is necessary, while a small deviation results in strong change in the stabilized phase [33]. As compared to planar film deposition, effects on the layer composition and crystal structure are expected to be different for HAR structures.…”
Section: Resultsmentioning
confidence: 99%